2012
DOI: 10.1021/jp307442f
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen-Bonding Ability of the Amino Acid Glutamine Revealed by Neutron Diffraction Experiments

Abstract: Hydrogen bonding between glutamine residues has been identified as playing an important role in the intermolecular association and aggregation of proteins. To establish the molecular mechanisms of glutamine interactions, neutron diffraction coupled with hydrogen/deuterium isotopic substitution in combination with computational modeling has been used to investigate the structure and hydration of glutamine in aqueous solution. The final structures obtained are consistent with the experimental data and provide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 50 publications
5
70
1
Order By: Relevance
“…For Gln, we assume that the Gaussian centered at χ 3 ∼ −13° is the physically relevant solution based on the neutron diffraction study of Rhys et al 58 For Gln 3 and Asp 2 -Gln 10 -Lys 2 , we conclude that the Gaussians centered at negative χ 3 angles correspond to the physically relevant solutions to eq 3 because they fall within the range of χ 3 dihedral angles most commonly adopted by Gln residues that populate PPII (Φ, Ψ) angles (Figure 7c). …”
Section: Resultsmentioning
confidence: 99%
“…For Gln, we assume that the Gaussian centered at χ 3 ∼ −13° is the physically relevant solution based on the neutron diffraction study of Rhys et al 58 For Gln 3 and Asp 2 -Gln 10 -Lys 2 , we conclude that the Gaussians centered at negative χ 3 angles correspond to the physically relevant solutions to eq 3 because they fall within the range of χ 3 dihedral angles most commonly adopted by Gln residues that populate PPII (Φ, Ψ) angles (Figure 7c). …”
Section: Resultsmentioning
confidence: 99%
“…NDIS is a well-established technique which has been used successfully to determine the atomistic interactions between a range of molecules and water in solution. [18][19][20][23][24][25][26][27][28][29] Neutron diffraction measurements provide a direct measure of the structure in reciprocal space -the static structure factor, F(Q). F(Q) can be written as:…”
Section: Neutron Diffraction With Isotopic Substitutionmentioning
confidence: 99%
“…However, recently it has been shown that investigations into the structure and hydration of small biological molecules in solution can yield valuable insights into how these molecules may function in nature. [18][19][20] In the current work, the structure and conformation of cocaine hydrochloride has been investigated in aqueous solution on the atomic scale using a combination of neutron diffraction enhanced by isotopic substitution and computation. Understanding the details of drug interactions with aqueous environments will increase the comprehension of the mechanisms responsible for how small molecules permeate into the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…Both SANS and wideangle scattering studies were carried out on the same solutions and although the formation of larger transient clusters of proline [38,39] and glutamine [40] were observed during modelling of the wide angle scattering data and in MD simulations, no larger scale structures were found in the SANS data.…”
Section: Solution Self-assembly Of Larger Amphiphilesmentioning
confidence: 99%